Superior electrocatalytic ORR performance of Melaleuca Leucadendron L barks derived hierarchical porous carbon with abundant atom-scale vacancies and multiheteroatoms. Issue 8 (15th April 2022) - He, Song; Li, Ming; Lin, Xiaoying; Li, Tao; Tan, Furui; Hao, Shiji; Yang, Zhenyu; Cui, Lifeng; Sun, Chenghua; Xu, Yongjun; Ke, Yubin; Zhu, Deliang; et al.
Abstract: Biomass feedstocks from agriculture and forestry usually possess unique isometric microstructures that are used as potential renewable precursors to synthesize hierarchically porous carbon materials for energy-conversion applications. Herein, the powders of Melaleuca leucadendron L. barks (MLBs) impregnated with a hydrogen bonded complex (HBC) were carbonized to prepare CoBN-doped porous carbon (CBNC) as oxygen reduction reaction (ORR) electrocatalysts. The microstructure, porous texture and compositions of the as-obtained CBNC samples and their intermediates were characterized by small-angle neutron scattering (SANS) and other techniques. The lamellar structure of MLBs and the HBC strategy endowed the as-obtained CBNC with a unique porous texture, large specific surface area (1041 m 2 g −1 ) and uniformly distributed heteroatoms of Co, B and N. The introduction of Co species in the precures is beneficial to improving the formation of atomic defects. The CBNC sample obtained at the optimized conditions exhibited a half-wave potential ( E 1/2 ) of 0.83 V and a kinetic current density ( j k ) of 9.73 mA cm −2 as well as a robust durability and methanol tolerance in the alkaline electrolyte; its overall ORR properties were highly superior to Pt/C ( j k = 8.2 mA cm −2, E 1/2 = 0.82 V). This novel approach offers a feasible way towards producing high-performance ORR electrocatalysts from biomass wastes.